Kelarutan Zat Warna Organik dalam Gelasi Mikroemulsi Water In Oil dari Sistem Air, Surfaktan Nonionik (Brij 35) dan Pentanol - Hanny Sri Asih; Ananda Putra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Research on solubility from organic pigments of turmeric (Curcuma longa Linn) and telang flower (Clitoria ternatea L.) in water-in-oil microemulsion gelation on system of water, nonionic surfactant (Brij 35) and pentanol has been studied. The purpose of this research was the preparation of water-in-oil microemulsion gelation, determines solubility, density, and bias index of organic pigments in water-in-oil microemulsion gelation on system of water, nonionic surfactant (Brij 35) and pentanol. The method used is the sol-gel method. The  solubility in water-in-oil microemulsion gelation of turmeric is 2,41832% (pH 4,5) and 2,61402% (pH 9,5) and telang flower is 1,21274%  (pH 4,5) and 1,6136% (pH 9,5). The bias index of turmeric is 1,4024 (pH 4.5) and 1,4034 (pH 9,5) and telang flower is 1,4004  (pH air 4,5) and 1,4014 (pH 9,5).The density of turmeric is 0,88778g/cm3 (pH 4,5) and 0,88912g/cm3 (pH 9,5) and telang flower is 0,8793g/cm3 (pH 4,5) and  0,8872g/cm3 (pH 9,5).